Implementation outcomes of the waves for change community-based task-shared prevention intervention for adolescent mental health in South Africa - Thandi Davies; Jamie Marshall; Nicola van der Merwe; Paula Yarrow; Tim Conibear; Crick Lund (Cambridge Prisms: Global Mental Health)
Adolescents face increased vulnerability to mental health conditions, particularly when exposed to multidimensional poverty and trauma and pronounced treatment gaps. Waves for Change, a Sport for Development (SfD) intervention, employs task-sharing through its ‘5-Pillar Method’ to build resilience and prevent mental health conditions among at-risk adolescents in South Africa. This study assessed the implementation outcomes of this Method using a mixed-methods design, incorporating interviews, focus groups, self-report questionnaires, document reviews and routine site assessments, with 69 stakeholders including staff, peer coaches, mental healthcare providers, social workers, teachers, and adolescents. A thematic analysis revealed key facilitators to successful implementation, including: a year-long preventative approach, creation of safe spaces for learning self-regulation skills, employment of youth coaches from local communities, incorporation of fun, group-based physical activities, modelling and repetition of desired skills, provision of transport and meals, government partnerships, and consistent weekly training and supervision. Implementation challenges included coach capacity, due to their education levels and own trauma experiences, measurement of fidelity to the Method and of adolescents’ emotional experiences, and some concerns around ocean safety. These findings provide valuable insights for implementing community-based SfD interventions for adolescents facing adversity, and contributes towards global evidence supporting task-shared mental health approaches in LMICs.